Participation in gardening activity and its association with improved mental health among family caregivers of people with dementia in rural Uganda - Herbert, E. Ainamani...[et al] (Preventive Medicine Reports, 2021)
Evidence from high-income settings suggests that gardening is associated with reductions in depression, anxiety, and stress. The benefits of gardening are less well understood by mental health practitioners and researchers from low- and middle-income countries. Our study estimated the association between participation in gardening and symptoms of depression, anxiety, and stress among caregivers of people living with dementia in rural, southwestern Uganda. In a cross-sectional study, we interviewed 242 family caregivers of people with dementia to elicit their gardening activities; symptoms of depression, anxiety, and stress (Depression Anxiety Stress Scales); and caregiving burden (Zarit Burden Interview). Linear multivariable regression models estimated the association between participation in gardening and symptoms of depression, anxiety, and stress. Out of 242 participants, 131 (54%) caregivers were involved in gardening. Severe to extremely severe symptoms of depression were less prevalent among those who were involved in gardening compared with those who were not (0 [0%] vs. 105 [95%], P < 0.001), as were severe to extremely severe symptoms of anxiety (36 [27%] vs. 110 [99%], P < 0.001) and stress (2 [2%] vs. 94 [85%], P < 0.001). In regression models adjusting for covariates,we found statistically significant associations between participation in gardening and symptoms of depression (b = -18.4; 95% CI, 20.5 to 􀀀 16.3), anxiety (b = -16.6; 95% CI, 􀀀 18.6 to –14.6), and stress (b = -18.6; 95% CI, 􀀀 20.6 to –16.6). Caregivers of people with dementia who participate in gardening have lower symptoms of depression, anxiety, and stress. Gardening interventions in this at-risk population may ameliorate symptoms of depression, anxiety, and stress.